Gastrulation EMT Is Independent of P-Cadherin Downregulation. - Pricila K Moly; James R Cooley; Sebastian L Zeltzer; Tatiana A Yatskievych; Parker B Antin (PLoS ONE, 2016)
Epithelial-mesenchymal transition (EMT) is an evolutionarily conserved process during which cells lose epithelial characteristics and gain a migratory phenotype. Although downregulation of epithelial cadherins by Snail and other transcriptional repressors is generally considered a prerequisite for EMT, recent studies have challenged this view. Here we investigate the relationship between E-cadherin and P-cadherin expression and localization, Snail function and EMT during gastrulation in chicken embryos. Expression analyses show that while E-cadherin transcripts are detected in the epiblast but not in the primitive streak or mesoderm, P-cadherin mRNA and protein are present in the epiblast, primitive and mesoderm. Antibodies that specifically recognize E-cadherin are not presently available. During EMT, P-cadherin relocalizes from the lateral surfaces of epithelial epiblast cells to a circumferential distribution in emerging mesodermal cells. Cells electroporated with an E-cadherin expression construct undergo EMT and migrate into the mesoderm. An examination of Snail function showed that reduction of Slug (SNAI2) protein levels using a morpholino fails to inhibit EMT, and expression of human or chicken Snail in epiblast cells fails to induce EMT. In contrast, cells expressing the Rho inhibitor peptide C3 rapidly exit the epiblast without activating Slug or the mesoderm marker N-cadherin. Together, these experiments show that epiblast cells undergo EMT while retaining P-cadherin, and raise questions about the mechanisms of EMT regulation during avian gastrulation.